2022
DOI: 10.48550/arxiv.2207.14265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seeing sharper and deeper: JWST's first glimpse of the photometric and spectroscopic properties of galaxies in the epoch of reionisation

Abstract: We analyse the photometric and spectroscopic properties of four galaxies in the epoch of reionisation (EoR) within the SMACS 0723 JWST Early Release Observations field. Given the known spectroscopic redshifts of these sources, we investigated the accuracy with which photometric redshifts can be derived using NIRCam photometry alone, finding that F115W imaging is essential to distinguish between 𝑧 ∼ 8 galaxies with high equivalent width (EW) [O III] 𝜆5007 emission and 𝑧 ∼ 10 Balmer break galaxies. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
(112 reference statements)
2
10
0
Order By: Relevance
“…Our redshift measurements are consistent with the values previously measured by other groups (e.g. Curti et al 2022, Carnall et al 2022, Atek et al 2022, Katz et al 2022, Trussler et al 2022.…”
Section: Search For Protocluster Behind Smacs0723supporting
confidence: 92%
“…Our redshift measurements are consistent with the values previously measured by other groups (e.g. Curti et al 2022, Carnall et al 2022, Atek et al 2022, Katz et al 2022, Trussler et al 2022.…”
Section: Search For Protocluster Behind Smacs0723supporting
confidence: 92%
“…This possibly indicates that we enter at 𝑧 > 7 another epoch of galaxy formation, where galactic systems are out of equilibrium and evolve more stochastically. Consistent with this, other studies find high ionization, low metallicity and high pressure in the interstellar medium (ISM; Katz et al 2022;Schaerer et al 2022;Rhoads et al 2022;Trump et al 2022;Trussler et al 2022).…”
Section: Introductionsupporting
confidence: 71%
“…These three objects have been discussed in several recent papers (e.g., Arellano-Córdova et al 2022;Carnall et al 2022;Curti et al 2022;Katz et al 2022;Rhoads et al 2022;Schaerer et al 2022;Trump et al 2022;Trussler et al 2022). The different studies rely on different measurement techniques, but also on different reduction and calibration pipelines, making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of these z ∼ 9 − 16 candidates observed in JWST imaging further reveal young stellar ages ∼ 10−100 Myr (Whitler et al 2022;Furtak et al 2022), younger than the median ages ∼ 100 Myr measured at slightly lower redshifts z ∼ 7 − 9 (Leethochawalit et al 2022;Endsley et al 2022). Evidence that some of these galaxies are extremely young, < 10 Myr, z ∼ 7 − 9 is provided by very strong emission lines in NIRSpec spectroscopy (Carnall et al 2022;Tacchella et al 2022;Trussler et al 2022), with flux excesses also clearly observed in photometry, especially when imaging is available in four NIRCam long-wavelength filters F277W, F356W, F410M, and F444W.…”
Section: Introductionmentioning
confidence: 99%